Adsorption properties of porous Langmuir-Blodgett layer used in SAW sensor for vapors of some chlorinated hydrocarbons - BALCERZAK, Andrzej (Archives of Acoustics, 2009)
The porous Langmuir-Blodgett film has been fabricated from an equimolar mixture of 5-[[1,3-dioxo-3- [4- (1-oxooctadecyl) phenyl] propyl] amino] - 1,3 - benzenedicarboxylic acid (DA) with cetylamine (CA) and subsequently removing of cetylamine after a layer deposition. This film has been investigated as the sensing layer of the surface acoustic waves (SAW) sensor of vapors of some chlorinated hydrocarbons in air. From the experimental results the values of the number of adsorbed molecules of chlorinated hydrocarbons per surface of sensing layer, NM/A, for this porous Langmuir-Blodgett layer has been calculated. An attempt to explain the observed differences in the adsorption of chlorinated hydrocarbons has been undertaken.